Digital Platforms as Catalysts for Innovation in Infection Surveillance and Telemedicine - Subhash Manohar Chodhary,; Rajender Singh Khatana,; Dr. Puneet,; Dr. Shiv Kumar, (International Journal of Scientific Research in Science and Technology, 2025)
Digital platforms are playing a transformative role in modern healthcare, especially in expanding access and enhancing the efficiency of medical services. Telemedicine and mobile health (mHealth) technologies have emerged as key innovations, enabling remote diagnostics, consultation, treatment, and monitoring. With real-time data sharing, wearable biosensors, AI-powered diagnostics, and secure video consultations, these technologies are bridging the gap between healthcare providers and patients, particularly in underserved regions. India has been a notable participant in this digital health revolution, launching multiple public and private initiatives since the early 2000s. These include mobile telemedicine units like The Bike Doc, digital clinics, the National Telemedicine Portal, and partnerships with international networks. Government programs such as the Integrated Disease Surveillance Project (IDSP), Village Resource Centres (VRCs), and the AROGYASREE platform exemplify India’s commitment to leveraging digital technologies for public health. Additionally, telemedicine supports infection prevention through electronic monitoring systems, smart EMRs, and machine learning–based decision support tools. Key infection control practices such as PPE use, hand hygiene, and environmental cleanliness are now integrated with digital protocols for better compliance and accountability. Despite infrastructure challenges and limited awareness, telemedicine has shown substantial promise in disaster response, chronic disease management, and education. As wireless technologies and health data standards advance, telemedicine is expected to achieve broader implementation, both nationally and globally, contributing significantly to equitable and resilient healthcare systems.
Keywords: Infection surveillance; remote monitoring; public health; mobile health units; e-health; AI diagnostics